Efektivitas penerapan pendekatan saintifik (Scientific Learning) terhadap kemampuan berpikir kritik dan pemecahan masalah matematika: Studi Eksperimen pada Siswa Kelas XI SMK Pelayaran di Jakarta Utara - Abd. Kadir Djaelani (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
The purpose of this study was to determine the effect of the scientific learning approach on students' ability to think critically and solve mathematical problems in a multivariate manner, the influence of scientific learning approaches on students' mathematical critical thinking abilities, and the influence of scientific learning approaches on students' mathematical problem solving abilities. The research method used is an experiment, the sampling technique uses multistage sampling, the data collection technique uses a critical thinking ability test and a problem-solving ability test. Data analysis was performed using MANOVA (Multivariate Analysis of Variance) statistics. The results of the study concluded: (1) There is a significant effect of the scientific learning approach (scientific learning) on the ability to think critically and solve mathematical problems. (2) There is a significant effect of scientific learning approach (scientific learning) on the ability to think of mathematical criticism. (3) There is a significant effect of scientific learning approach (scientific learning) on the ability to solve mathematical problems. In an effort to improve mathematical critical thinking skills, the scientific learning approach to the discovery learning model is more effective than the problem-based learning scientific approach, while the mathematical problem solving ability of the scientific learning approach to problem-based learning models is more effective than the scientific learning approach discovery learning models.